Introductory marketing - Page, Stephen ([S.l.] : Nelson Thornes Ltd, 1995)
Although this text guides the student through the essential theory, its emphasis is on an interactive approach which shows how marketing works in practice. At key points there are discussion points and case studies combined with activities and assignments to develop and reinforce knowledge and skill. The discussion ranges from market research and consumer behaviour to the key elements of the marketing mix, international marketing and the legal dimension, before concluding with marketing planning.
Keywords: marketing